ANALISIS KELENGKAPAN PRODUK, KUALITAS LAYANAN, DAN TATA LETAK TERHADAP KEPUASAN KONSUMEN PADA MINIMARKET JAKARTA SELATAN - Siti Hawa; Alfatih Sikki Manggabarani; Heni Nastiti (Prodi Magister Manajemen Fakultas Ekonomi dan Bisnis Universitas Bhayangkara Jakarta Raya, 2022)
Minimarkets are modern stores that provide basic needs by placing outlets near people's residences. This study is a quantitative study designed to determine, prove, and analyze whether consumer satisfaction at minimarkets is influenced by product completeness, service quality, and layout. With a population of minimarket (Indomaret and Alfamart) consumers in Cilandak District, South Jakarta. With a sample of 100 respondents using non-probability sampling method with purposive sampling type. Collecting data by distributing questionnaires via google form. The data analysis technique used Partial Least Square (PLS). The results showed that the product completeness variable had a significant effect on consumer satisfaction with a path coefficient of 0.268, service quality had a significant effect with a path coefficient of 0.298, and layout had a significant effect with a path coefficient of 0.358, meaning that it had a partial and significant effect on consumer satisfaction. Analysis of the coefficient of determination explains that product completeness, service quality, and layout affect customer satisfaction at the South Jakarta Minimarket by 74.6%, the remaining 25.4% is influenced by other variables.